Fast Sodium‐Ion Conductivity in Supertetrahedral Phosphidosilicates. (2nd May 2018) - Haffner, Arthur; Hatz, Anna‐Katharina; Moudrakovski, Igor; Lotsch, Bettina V.; Johrendt, Dirk
Abstract: Fast sodium‐ion conductors are key components of Na‐based all‐solid‐state batteries which hold promise for large‐scale storage of electrical power. We report the synthesis, crystal‐structure determination, and Na + ‐ion conductivities of six new Na‐ion conductors, the phosphidosilicates Na19 Si13 P25, Na23 Si19 P33, Na23 Si28 P45, Na23 Si37 P57, LT ‐NaSi2 P3 and HT ‐NaSi2 P3, based entirely on earth‐abundant elements. They have SiP4 tetrahedra assembled interpenetrating networks of T3 to T5 supertetrahedral clusters and can be hierarchically assigned to sphalerite‐ or diamond‐type structures. 23 Na solid‐state NMR spectra and geometrical pathway analysis show Na + ‐ion mobility between the supertetrahedral cluster networks. Electrochemical impedance spectroscopy shows Na + ‐ion conductivities up to σ (Na + )=4×10 −4 S cm −1 . The conductivities increase with the size of the supertetrahedral clusters through dilution of Na + ‐ions as the charge density of the anionic networks decreases. Abstract : Netzwerke aus großen supertetraedrischen Phosphidosilicatclustern ermöglichen schnelle Na + ‐Ionenleitung in den Verbindungen Na23 Si9 n +19 P12 n +33, die vollständig auf häufigen und leicht zugänglichen Elementen beruhen. Die Leitfähigkeiten steigen mit der Größe der Supertetraedercluster infolge einer Verdünnung der Na + ‐Ionen auf bis zu 4×10 −4 S cm −1, was vergleichbar mit den Werten bekannter fester Ionenleiter ist.